Republic of Mozambique : Fifth Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2003)
Mozambique's economic program was originally supported by a three-year arrangement under the Enhanced Structural Adjustment Facility (ESAF). The Mozambican authorities are to be commended for a continued satisfactory performance under their Poverty Reduction Growth Facility (PRGF)-supported program. When the IMF program completed the fifth review, the Executive Board welcomed the important measures that the authorities have taken to strengthen government revenue, including the adoption of new tax codes and the increase in fuel taxes to correct the erosion from past inflation.